Effect of community interventions on social-communicative abilities of preschoolers with autism spectrum disorder. (3rd May 2016) - Van der Paelt, Sara; Warreyn, Petra; Roeyers, Herbert
Abstract: Purpose : To evaluate the effect that different intervention methods have on the social-communicative abilities of children with autism spectrum disorder (ASD) in community settings. Methods : Intervention based on applied behaviour analysis was compared with a more specific intervention programme targeting imitation and joint attention (JA) and with treatment as usual in a sample of 85 children with ASD. Objective measures for imitation, JA, pretend play, language, autism severity and parent report measures were used to assess the effect of six months of intervention. Results : Results revealed no differences between the intervention methods. There was, however, great individual variability in outcome within each treatment method. Conclusion : These results suggest that it is important to focus on "What works for whom" instead of trying to find a one-size-fits-all-treatment for children with ASD.